An Optimal Analysis of Cloud-based Secure Web Applications: A Systematic Exploration based on Emerging Threats, Pitfalls and Countermeasures - Muhammad Saeed Liaqat; Nayab Sharif; Asfar Ali; Hussnain Khan; Hafiz Nabeel Ahmed; Hamayun Khan (Spectrum of Engineering Sciences, 2024)
Web applications are one of the most prevalent platforms for information and service delivery over the Internet today. As they are increasingly used for critical services, web applications have become a popular and valuable target for security attacks. The center of mass for newly-released applications is shifting from traditional, desktop or server programs, toward web and cloud computing applications. This shift is favorable to end-users, but puts additional burden on application developers and service providers. The exponential growth and capillar diffusion of the Web are nurturing a novel generation of applications, characterized by a direct business-to-customer relationship. Web applications have come to occupy a pivotal role in how individuals and groups access information and carry out vital functions, yet their widespread adoption has been accompanied by deepening dangers from malign forces seeking to compromise users and inflict harm. This wide-ranging literature review aims to shed light on emerging perils to web application security and the counteroffensives devised to turn them back. An exhaustive process was undertaken of gathering academic papers, conference proceedings, and industry reports before conducting a probing analysis and synthesis. The findings highlight how vulnerabilities in web applications endure, exposing them to misuse at the hands of virulent actors. Despite progress in security technologies, novel deficiencies emerge as web applications evolve to meet rapidly changing needs and breakthroughs. The review underscores the demand for adaptive and agile security frameworks with the dexterity to adjust to the shape-shifting nature of web application threats. An executive summary conveys the key takeaways through tables and figures illuminating rising dangers and matching safeguards. The conclusions emphasize how proactive and resilient security measures must be reinforced to shield web applications in an environment growing ever more intricate and inimical. Keywords- Cyber security, Web Application Security, SQL Injection, Machine Learning, Block Chain, Artificial Intelligence, IoT, Threats, Detection Methods, Vulnerabilities, Coding.